The Correlation between Elbow and Parturition Bed Height with the Risk of Musculoskeletal Disorders - Hilfia Alifa Nurly; Mulyono Mulyono (Universitas Airlangga, 2020)
Introduction: Ergonomics can potentially cause harms for workers. Midwives are among those workers who are susceptible to have an impaired performance by ergonomics. As health professionals whose main task are providing care during childbirth, 40.8% of midwives suffer from musculoskeletal disorders at neck and 24.5% on upper back due to poor repetitive and frequent work posture they need to do over a long time while assisting childbirth such as bending, tilting the body to the left and looking toward the birth canal. A study claimed that midwives had a very high risk to suffer from MSDs. This study aimed at analyzing the correlation between elbow and parturition bed height with the risk of musculoskeletal disorders among midwives while assisting childbirth at the hospital. Method: This cross-sectional design research was determined using non-probability sampling technique involving 11 midwives in the hospital delivery room. The examined variables covered age, period of working, anthropometry, parturition bed, posture, and MSDs using a measurement sheet, REBA and Nordic Body Map Questionnaire as the research instruments. The data is presented in the cross tabulation from computer analysis data program and in description. Results: As much as 91 % midwives were at the age of 26-45 years old with >10 years of experience that was about 72.7%; 3 midwives had BMI score > 29; 81.8% midwives had high score level of musculoskeletal disorders risk, 81.8% midwives did not set their parturition bed with appropriate elbow height; and the value of contingency coefficient from elbow and parturition bed height with musculoskeletal disorders was 0.707. Conclusion: There is correlation between elbow and parturition bed height with musculoskeletal disorder of midwives when assisting childbirth process at hospital.Keywords: childbirth, ergonomics, midwife, musculoskeletal disorders